Mating system of Biomphalaria sudanica, a vector of Schistosoma mansoni - Jenessa Olson; Tom Pennance; Johannie M. Spaan; Maurice R. Odiere; Jacob A. Tennessen; Michelle L. Steinauer (Current Research in Parasitology and Vector-Borne Diseases)
Biomphalaria snails are intermediate hosts for schistosome parasites, which cause morbidity and mortality in humans worldwide. We aimed to determine the mating system of Biomphalaria sudanica, a hermaphroditic vector of schistosomiasis in the African Great Lakes, with the goal of informing the design of genetic studies such as linkage mapping to improve genome assembly and genetic association studies to identify snail resistance genes. To determine the relative rates of outcrossing versus selfing, we assayed the progeny of experimental crosses of snails in the laboratory using a PCR and restriction enzyme digest to determine snail genotype and parentage. Out of 7 experimental crosses and 56 total offspring assayed, 100% were derived from outcrossing rather than inbreeding. These results indicate that B. sudanica is primarily an outcrossing species, although previous work has shown that this species retains the capability of self-fertilization.